Bacillus cereus Biofilms—Same, Only Different - Majed, Racha; Faille, Christine; Kallassy, Mireille; Gohar, Michel (Frontiers in Microbiology, 2016)
Bacillus cereus displays a high diversity of lifestyles and ecological niches and include beneficial as well as pathogenic strains. These strains are widespread in the environment, are found on inert as well as on living surfaces and contaminate persistently the production lines of the food industry. Biofilms are suspected to play a key role in this ubiquitous distribution and in this persistency. Indeed, B. cereus produces a variety of biofilms which differ in their architecture and mechanism of formation, possibly reflecting an adaptation to various environments. Depending on the strain, B. cereus has the ability to grow as immersed or floating biofilms, and to secrete within the biofilm a vast array of metabolites, surfactants, bacteriocins, enzymes, and toxins, all compounds susceptible to act on the biofilm itself and/or on its environment. Within the biofilm, B. cereus exists in different physiological states and is able to generate highly resistant and adhesive spores, which themselves will increase the resistance of the bacterium to antimicrobials or to cleaning procedures. Current researches show that, despite similarities with the regulation processes and effector molecules involved in the initiation and maturation of the extensively studied Bacillus subtilis biofilm, important differences exists between the two species. The present review summarizes the up to date knowledge on biofilms produced by B. cereus and by two closely related pathogens, Bacillus thuringiensis and Bacillus anthracis. Economic issues caused by B. cereus biofilms and management strategies implemented to control these biofilms are included in this review, which also discuss the ecological and functional roles of biofilms in the lifecycle of these bacterial species and explore future developments in this important research area.